All can be saved: religious tolerance and salvation in the Iberian Atlantic world - Schwartz, Stuart B. (Yale Univ. Press, 2008)
Iberian doubts -- Propositions -- Conversos and moriscos -- Christian tolerance -- Portugal : old Christians and new Christians -- American liberties -- American propositions : body and soul in the Indies -- American adjustments -- Brazil : salvation in a slave society -- Toward toleration -- From tolerance to toleration in the eighteenth-century Iberian Atlantic world -- Rustic pelagians